Kegiatan Pelakasanaan Pembelajaran PJOK di SD Negeri 060874 Medan - Suyono, Suyono; Ramadhani, Fitri; Siregar, Amandha Fhadillah; Azahra, Zelma (ALACRITY : Journal of Education, 2024)
Physical education is an integral part of the overall education system. This educational process utilizes physical activity to produce holistic changes in individual qualities both physically, mentally and emotionally. The motive for this research was to determine the implementation of physical education, sports and health learning activities at SD Negeri 060874 Medan City. This type of research is qualitative. Data collection techniques through observation, interviews and documentation. The results of the research are 1) The indicator for learning objectives is categorized as "sufficient" with a percentage achievement of 60.0%. 2) The indicator for learning materials is categorized as "sufficient" with a percentage achievement of 60.0%. 3) The indicator for teaching methods is categorized as "sufficient" with a percentage achievement of 58.6%. 4) The indicator for learning media or tools is categorized as "good" with a percentage achievement of 60.5%. 5) The indicator for learning evaluation is categorized as "sufficient" with a percentage achievement of 55.8%.